Impact sound insulation of cross-laminated timber/massive wood floor constructions: Collection of laboratory measurements and result evaluation. Issue 1 (March 2017) - Homb, Anders; Guigou-Carter, Catherine; Rabold, Andreas
Wooden building systems, including cross-laminated timber elements, are becoming more common. The last few years have seen new developments and documentation of innovative types of cross-laminated timber floor assemblies. Regarding impact sound associated to walking persons, running or jumping children, such floor assemblies can be regarded as a weak part. So far, there are no reliable standardized calculation models available, for prediction of impact sound in the entire frequency range. Therefore the design is always based upon previous experiences and available measurements. This article presents the results of a number of well controlled sound insulation measurements of cross-laminated timber/massive wood floor constructions conducted in laboratories. The collection of data and results analysis highlight some basic phenomena. For instance, how structural differences related to the grouping of the constructions change the frequency distribution of the impact sound level and the single number quantities. Another significant result is the influence of the dynamic stiffness of the resilient interlayer of floating floor systems and the mass per unit area of the floors. Based on this analysis, the aim is to identify similarities and carry out simplifications. The data will be further processed and used in the development of prediction models and optimization process of cross-laminated timber floor assemblies.